The causal effects of an intensified curriculum on cognitive skills: Evidence from a natural experiment - Vincenzo Andrietti (Universidad Carlos III, 2016)
This paper exploits a unique universal educational policy - implemented in most German states between 2001 and 2008 - that compressed the academic-track high school curriculum into a (one year) shorter time span, thereby increasing time of instruction and share of curriculum taught per grade. Using 2000-2012 PISA data and a quasi-experimental approach, I estimate the impacts of this intensified curriculum on cognitive skills. I find robust evidence that the reform improved, on average, the reading, mathematical, and scientific literacy skills acquired by academic-track ninth graders upon treatment. However, I also provide evidence that the reform widened the gap in student performance with respect to parental migration background and student ability. Finally, although the reform did not affect, on average, high school grade retention, I find that the latter increased for students with parental migration background. Taken together, these findings suggest that moving to a compressed high-school curriculum did not compromise and benefited, on average, students' cognitive skills. However, they also raise equity concerns that policy-makers should be aware of.
hdl:10016/22880
Keywords: I21; I28; D04; 330; G8 reform; Intensified curriculum; Instruction time; Learning intensity; Cognitive skills; Academic-track high school; Grade retention; Remedial education